Constitutional law for a changing America - Epstein,Lee (Washinghon, 2010)
Constitutional Law for a Changing Americadraws on political science as well as legal studies to analyze and excerpt cases. With meticulous revising and updating throughout, Epstein and Walker streamline material while accounting for recent landmark cases and new scholarship.
Keywords: Civil rights-United states-cases